Impact of Foreign Direct Investment, Financial Development and Stock Market on Economic Growth: The Case of Turkey - Girinshuti, Honorine (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The purpose of this study is to investigate the relationship between foreign direct investment, financial development and stock market towards economic growth in Turkey. Various tests are applied in order to indicate the connection in between , Johansen co-integration test made on non-stationary variables indicate that there is a co-integrating vector as well as there might be a long term relationship among foreign direct investment, financial development, stock market and the dependent variable GDP concerning error correction model estimation. It is found that there is a long run equilibrium relationship among the variables. In long term, foreign direct investment and financial development are statistically significant at α=0.10.Which means that foreign direct investment and financial development have a positive impact on gross domestic product. Moreover, SM has a negative impact on GDP in Turkey for the long run.

ÖZ: Bu çalışmanın amacı, Türkiye’deki doğrudan yabancı yatırımlar, finansal gelişme, hisse senedi piyasası ve ekonomik büyüme arasındaki uzun dönemli denge ilişkisini incelemektir. Uzun dönemli denge ilişkisini göstermek için durağan olmayan değişkenler üzerinde Johansen eş bütünleşme testi uygulanmıştır. Johansen eş bütünleşme testi sonuçlarına göre doğrudan yabancı yatırımlar, finansal gelişme, hisse senedi piyasası ve ekonomik büyüme arasında uzun dönemli bir ilişki olduğu kanıtlanmıştır. Hata düzeltme modeli sonuçlarına göre uzun vadede doğrudan yabancı yatırımlar ve finansal gelişme değişkenleri α = 0.10'da istatistiksel olarak anlamlıdır. Bu sonuçlara göre doğrudan yabancı yatırımların ve finansal gelişmenin gayri safi yurtiçi hasıla üzerinde pozitif bir etki yarattığı bulunmuştur. Bunun yanında hisse senedi piyasasının uzun vadede ekonomik büyüme üzerinde olumsuz bir etkisi olduğu bulunmuştur.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2018. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Foreign Direct Investments--Turkey; Foreign direct investment; financial development; stock market and gross domestic product